2016
DOI: 10.1074/jbc.m115.710616
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plant-derived Alkaloids with Therapeutic Potential for Myotonic Dystrophy Type I

Abstract: Myotonic dystrophy type I (DM1) is a disabling neuromuscular disease with no causal treatment available. This disease is caused by expanded CTG trinucleotide repeats in the 3 UTR of the dystrophia myotonica protein kinase gene. On the RNA level, expanded (CUG) n repeats form hairpin structures that sequester splicing factors such as muscleblind-like 1 (MBNL1). Lack of available MBNL1 leads to misregulated alternative splicing of many target pre-mRNAs, leading to the multisystemic symptoms in DM1. Many studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…We also treated DU145 cells with the drug harmine, a multifunctional alkaloid derived from the plant Peganum harmala that has a range of effects including antimicrobial, antitumour, and hallucinogenic (Patel et al, 2010;Moloudizargari et al, 2013). Harmine is also a potent inhibitor of the splice factor DYRK1A (Göckler at al., 2009), and it causes changes in alternative splicing in vivo (Herrendorf et al, 2016). DU145 cells were treated with 1-5M harmine for six hours.…”
Section: Effect Of Heat Shock Osmotic Shock and Harmine On Clk1 Altementioning
confidence: 99%
“…We also treated DU145 cells with the drug harmine, a multifunctional alkaloid derived from the plant Peganum harmala that has a range of effects including antimicrobial, antitumour, and hallucinogenic (Patel et al, 2010;Moloudizargari et al, 2013). Harmine is also a potent inhibitor of the splice factor DYRK1A (Göckler at al., 2009), and it causes changes in alternative splicing in vivo (Herrendorf et al, 2016). DU145 cells were treated with 1-5M harmine for six hours.…”
Section: Effect Of Heat Shock Osmotic Shock and Harmine On Clk1 Altementioning
confidence: 99%
“…HSA LR mice also recapitulate DM1 molecular characteristics such as foci accumulation, MBNL1 sequestration, and splicing abnormalities (5,7,8). Therapeutic strategies have mainly focused on targeting DM1-associated mis-splicing and mRNA toxicity (9)(10)(11), although a more complete understanding of pathogenic pathways would clearly be of interest for the development of alternative or additional therapeutic options. Recently, deregulation of cellular processes and signaling pathways important for maintaining proper muscle homeostasis has been reported in DM1.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic alkaloids can interact with RNA, and indeed berberine and harmine (Table 1 ) have been reported to bind RNA structures ( 78 , 79 ). In DM1 myoblasts, harmine reduced foci, nevertheless it did not improve the histology in gastrocnemius muscle of the HSA LR mice, as the percentage of fibers with internalized nuclei was not altered by the treatment of the mice with the compound ( 77 ). However, although harmine increased the levels of MBNL1 in DM1 myoblasts and enhanced MBNL1-dependent alternative splicing of cTNT E5, INSR E11, and Clcn1 E7a (Table S1 in Supplementary Material), a similar effect was found in wild-type myoblasts, suggesting that inhibition of the CUG–MBNL1 complex is not the primary MoA of this alkaloid.…”
Section: Small Molecules Of Natural Originmentioning
confidence: 87%
“…However, only a few studies have reported utilization of molecules of natural origin ( 40 , 76 ). Recently, a set of plant-derived alkaloids was identified as small molecules with an anti-DM1 effect ( 77 ). Using a novel CUG 78 –MBNL1 complex inhibition assay, a collection of isolated natural compounds and extracts from plants and fungal strains was screened.…”
Section: Small Molecules Of Natural Originmentioning
confidence: 99%